Эстетика и литературная критика - Аксаков К. С. (История эстетики в памятниках и документах, 1995)
Экземпляры: ЧЗ (20180904) / Инвентарный номер: 32691 / Цена: 18000 / Сис.шифр: 833.3(2Рос=Рус) / Авт.знак: А41 / ГРНТИ: 17 / ББК: 833.3(2Рос=Рус)-017